PENETAPAN KADAR KALSIUM PADA BEDAK TABUR DARI BAHAN BAKU CANGKANG KERANG BULU (Anadaraantiquata) SECARA KOMPLEKSOMETRI - Nurbaya, Siti; Sianipar, Artha Yuliana; Sitorus, Elly Nurita; Situmorang, Winton F. (Jurnal Farmanesia, 2017)
Until now, the utilization of clamshell waste has been limited to handicraft materials, whereas shellfish waste has a high calcium carbonate composition of about 98% which can be used as a source of calcium in the synthesis of compounds containing calcium metal. The purpose of this study was to determine the level of calcium contained in the shells of mussels and to determine the levels of calcium in the preparation of talcum powder which was added with powdered shells of feathers as an abrasive. Complexometric titration is also used to determine calcium levels in powder preparations formulated with feather shells powder. The results showed that the shells of feather shells contained calcium levels of 19.49% while the loose powder preparations contained calcium levels of 1.475%. The test results of the research on the formulation of loose powder preparations met the physical evaluation requirements. The pH test on loose powder, namely pH 7, meets the requirements of SNI 16-4399-1996, the pH value of cream cosmetic products is required to range from 4.5 to 8.0. The fine degree test is qualified because the loose powder can pass the sieving using a 100 mesh.